Strong Lipschitz Condition and Error of the Euler Method
Theorem
Let’s assume that the solution Y(x) to the initial value problem {y′=f(x,y)y(x0)=Y0, defined in [x0,b]×R for f, is twice differentiable in [x0,b]. If f satisfies strong Lipschitz condition∣f(x,y1)−f(x,y2)∣≤K∣y1−y2∣
for all x0≤x≤b, y1,y2∈R, and K≥0, then for the solution {yn(xn):x0≤xn≤b} obtained by Euler’s method, we have
x0≤xn≤bmax∣Yxn−yh(xn)∣≤ϵ(b−x0)K∣ϵ0∣+[Kϵ(b−x0)K−1]τ(h)
where τ(h)=2h∥Y’’∥∞ and ϵ0=Y0−yh(x0).
To sum up what has been a lengthy explanation, there’s a slightly stronger condition than the Lipschitz condition that speaks to the accuracy of solutions derived from Euler’s method. Unlike the case with just the Lipschitz condition, which assumes continuity, the strong Lipschitz condition also considers differentiability.
yn:=y(xn)
Let’s denote the error at the nth step by ϵn:=Y(xn)−y(xn).
If we perform an 2th order Taylor expansion of Y(xn+1) with respect to xn, for some xn≤ξn≤xn+1,
Yn+1=Yn+hY’n+2h2Y’’(ξn)
Let’s conveniently denote it as τn:=2hY’’(ξn),
Yn+1=Yn+hY’n+hτn
nmax∣τn∣≤τ(h)
Subtracting the equation obtained by Euler’s method, yn+1=yn+hf(xn,yn), from both sides,
Yn+1−yn+1=Yn−yn+h(f(xn,Yn)−f(xn,yn))+hτn
If we express it in terms of ϵn,
ϵn+1=ϵn+h(f(xn,Yn)−f(xn,yn))+hτn
Taking the absolute value of both sides,
∣ϵn+1∣≤∣ϵn∣+h∣f(xn,Yn)−f(xn,yn)∣+h∣τ(h)∣
By the Lipschitz condition,
∣ϵn+1∣≤∣ϵn∣+hK∣Yn−yn∣+h∣τ(h)∣
To summarize,
∣ϵn+1∣≤(1+hK)∣ϵn∣+h∣τ(h)∣
Solving it recursively,
∣ϵn+1∣≤(1+hK)n∣ϵ0∣+[1+(1+hK)+⋯+(1+hK)n−1]h∣τ(h)∣
By the Sum formula of a finite geometric series,
∣ϵn+1∣≤(1+hK)n∣ϵ0∣+[hK(1+hK)n−1]h∣τ(h)∣
According to a corollary of Bernoulli’s inequality, because (1+hK)n≤ehKn,
∣ϵn∣≤e(b−x0)K∣ϵ0∣+[Ke(b−x0)K−1]τ(h)
■
Additional Conditions
Now, let’s think about adding a condition from ∣ϵn+1∣≤∣ϵn∣+hK∣Yn−yn∣+h∣τ(h)∣ due to the Lipschitz condition up to ∂y∂f(x,y)≤0. To beautify the expression,
∣ϵn+1∣≤(1+hK)∣ϵn∣+2h2∣Y’’(ξn)∣
By the Mean valuetheorem,
K=y1−y2f(x,y1)−f(x,y2)=∂y∂f(xn,ζn)
there exists ζn∈H{yh(xn),Y(xn)} that satisfies. If h is sufficiently small so that 1+h∂y∂f(xn,ζn)≥−1, then
∣ϵn+1∣≤∣ϵn∣+2h2∣Y’’(ξn)∣
Solving this inequality recursively as well,
∣ϵn∣≤∣ϵ0∣+2h2[∣Y’’(ξ0)∣+⋯+∣Y’’(ξn−1)∣]
Therefore,
∣ϵn∣≤∣ϵ0∣+2h2n∥Y’’∥∞
since nh=b−x0,
∣ϵn∣≤∣ϵ0∣+2h∥Y’’∥∞(b−x0)
This means that the condition ∂y∂f(x,y)≤0 has linearly reduced the upper bound of the error, which would have increased exponentially with respect to (b−x0) originally. Fortunately, many problems found in natural phenomena satisfy this assumption, thereby significantly reducing the error.
Atkinson. (1989). An Introduction to Numerical Analysis(2nd Edition): p347.
xi:=x0+ih↩︎